Successive and Finite Difference Method for Gray Scott Model - Manaa, Saad A.; Rasheed, Joli (Science Journal of University of Zakho, 2013)
In this paper, Gray-Scott model has been solved numerically for finding an approximate solution by Successive approximation method and Finite difference method. Example showed that Successive approximation method is much faster and effective for this kind of problems than Finite difference method.